(untitled) (Research, Society and Development, 2021)
The present study aims to verify whether dogs and cats submitted to dissociative anesthesia for elective orchiectomy may present alterations in the tear production and consequent lesions on the ocular surface. For this purpose, 40 animals, 22 cats and 18 dogs, underwent an ophthalmic semiotechnique composed of the evaluation of anterior and posterior chambers, fundscopy, Schirmer’s tear test (TLS) and fluorescein test. Subsequently, they underwent dissociative anesthesia, associating ketamine with diazepam or midazolam. Immediately at the end of the procedure, the fluorescein and TLS test was repeated. After 24 hours, a new ophthalmic evaluation was performed to compare the results obtained. There were no ophthalmic changes. With the use of diazepam, TLS remained within the normal range with a median of 19 mm / min, with a mean and standard deviation of 19.27 ± 3.01 mm / min for dogs and a median of 18 mm / min, with a mean and standard deviation of 19.05 ± 2.81 mm / min for cats. When using midazolam, the TLS of the dogs had a median of 19 mm / min, with a mean and standard deviation of 18.84 ± 2.69 mm / min and of the cats, they had a median of 18 mm / min with a mean and standard deviation of 18.37 ± 2.32 mm / min. The results found suggest that the use of dissociative anesthesia for short procedures does not significantly alter the tear production, nor does it cause eye injuries.